PRELIMINARY ASSESSMENT OF HANOI LAND SUBSIDENCE WITH REFERENCE TO GROUNDWATER DEVELOPMENT - Pham Huy Giao; E. Ovaskainen (International Association of Lowland Technology, 2000)
Hanoi is a lowland city in the sense that its elevation is much lower than the Red River level and the city needs to be protected by a long-standing dike system. The capital of Vietnam is currently enjoying a rapid economics, industrial and population growth. But it is also facing a lot of problems; one of those in groundwater resource; hence, the increase in groundwater pumping to sustain the city in the future is inevitable. Land subsidence due to groundwater withdrawal has already manifested itself in a few monitoring data of good quality. For the current situation, both underestimation and exaggeration of land subsidence caused by groundwater pumping may have a serious impact on groundwater and infrastructure development if this growing city. In this paper, a preliminary assessment and analysis of Hanoi land subsidence was done based on the initial results of investigations by both Vietnamese and foreign researchers. Emphasis was on the application of a fast and practically reliable technique based on a bilinear compression model and Terzaghi's consolidation equation in a primary assessment of Hanoi land subsidence.